The pathogenesis of chronic lymphocytic leukemia - Zhang, Suping; Kipps, Thomas J (Annual review of pathology, 2014)
Chronic lymphocytic leukemia (CLL) is characterized by the clonal expansion of CD5(+)CD23(+) B cells in blood, marrow, and second lymphoid tissues. Gene-expression profiling and phenotypic studies suggest that CLL is probably derived from CD5(+) B cells similar to those found in the blood of healthy adults. Next-generation sequencing has revealed recurrent genetic lesions that are implicated in CLL pathogenesis and/or disease progression. The biology of CLL is entwined with its microenvironment, in which accessory cells can promote leukemia cell growth and/or survival. Recently, much attention has been focused on the CLL B cell receptor (BCR) and on chemokine receptors that enable CLL cells to home to lymphoid tissues and to establish the leukemia microenvironment. Agents that can interfere with BCR signaling or chemokine-receptor signaling, or that target surface antigens selectively expressed on CLL cells, promise to have significant therapeutic benefit in patients with this disease.